First report of stripe rust (Puccinia striiformis f. sp. tritici) on wheat in Quebec, Canada - Rioux, Sylvie; Mimee, Benjamin; Gagnon, Annie-Ève; Hambleton, Sarah (Phytoprotection, 2015)
Stripe rust, Puccinia striiformis f. sp. tritici, is one of the world’s most important diseases of wheat. In Canada, stripe rust is found mainly in the western provinces (British Columbia, Alberta and Saskatchewan) and, more recently, in the provinces of Manitoba and Ontario. Here, we report the first detection of stripe rust on wheat in the province of Quebec, Canada. Leaves showing yellowish sporulation arranged in narrow stripes were found in wheat performance trials at the research station of Université Laval, in Saint-Augustin-de-Desmaures. Morphological identification was confirmed by several PCR assays targeting specific genomic sequences and a rDNA gene segment (ITS2/28S).